2020
DOI: 10.1111/risa.13476
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Natural Hazards Risk Analysis: Potential, Challenges, and Research Needs

Abstract: Artificial intelligence (AI) methods have seen increasingly widespread use in everything from consumer products and driverless cars to fraud detection and weather forecasting. The use of AI has transformed many of these application domains. There are ongoing efforts at leveraging AI for disaster risk analysis. This paper takes a critical look at the use of AI for disaster risk analysis. What is the potential? How is the use of AI in this field different from its use in non-disaster fields? What challenges need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…This is driven by developments in information and communication technology, including sensor and storage technology, coupled with developments in artificial intelligence (AI) and statistics, including data mining, machine learning, and statistical learning theory (e.g., Hastie, Tibshirani, & Friedman, 2017;Vapnik, 2013). Guikema (2020) discusses the use of AI methods in the context of natural hazards risk analysis. He highlights what characterizes settings where AI methods have shown success and points out challenges with using such methods in this context.…”
Section: Current Developments and Trendsmentioning
confidence: 99%
“…This is driven by developments in information and communication technology, including sensor and storage technology, coupled with developments in artificial intelligence (AI) and statistics, including data mining, machine learning, and statistical learning theory (e.g., Hastie, Tibshirani, & Friedman, 2017;Vapnik, 2013). Guikema (2020) discusses the use of AI methods in the context of natural hazards risk analysis. He highlights what characterizes settings where AI methods have shown success and points out challenges with using such methods in this context.…”
Section: Current Developments and Trendsmentioning
confidence: 99%
“…Using operational datasets to build predictive models will continue to face issues with messy and inconsistent patterns that could perpetuate errors in human assessments (Guikema, 2020). The decision trees presented in this study only showed the most significant variables by restricting the p value to 0.0001 to keep the diagrams tidy and easy to interpret.…”
Section: Applications and Limitations Of Decision Support Toolsmentioning
confidence: 96%
“…1). The region is characterized by a transitional snow climate that favours heavy snowfall and the formation of multiple persistent weak layers each season (Haegeli and McClung, 2007;Shandro and Haegeli, 2018). The park is located at approximately 51.3 • N, 117.5 • W. Elevations range from 805 to 3377 m, with the typical treeline vegetation band around Weather and snowpack data were generated with numerical weather prediction and physical snow cover models for each elevation band.…”
Section: Study Area and Periodmentioning
confidence: 99%
“…This data will facilitate the prediction of the emergency scenario and understand human behaviour by assessing underline patterns of media users. Social sensing has advantages over field surveys and interviews, as it gathers data from the public, not directly from the disaster responders, provides real-time data of the disaster scenario and facilitate in making a timely decision for mitigating the disaster and informing the public about evacuation plans [75].…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%